I Can Only Imagine: The Aborted Korean Ministry (1566–1571) of Father Gaspar Vilela, as Recounted by His Letter of 3 November 1571—An Illustration of Jesuit Attitudes on Notions of an Imagined Korea - Hayoung Wong (Religions)
This article features an interdisciplinary analysis of the aborted Korean apostolate plan (1566–1571) described by the Jesuit missionary Gaspar Vilela (c. 1525–1572) in a letter dated 3 November 1571. This analysis’s foundation rests on Jesuit assumptions regarding the conception of an imagined Korea, a construct that Vilela discerned upon with a confidence that emanated from his awareness of the Jesuit order’s political power. The notion of an imagined Korea arguably drew from a creativity implied by the missionary imagination, an idea evidenced in thinking processes of perspective, positive/negative consubstantiality, radical self-assessment, and reduction advocated by anthropologists increasingly willing to engage with theology. Although Vilela’s plan seems far removed from the relativism of today’s more empathetic missionaries, the letter nonetheless emphasized a somewhat flexible mindset that contravened the ideas of more dogmatic Jesuit Europhiles. The 1571 Vilela letter captured the aspirational rhetoric of the Jesuits who dreamed about Korea, but these missionaries had not yet faced the adversities that would ultimately extinguish the missionary order’s already fragile hopes for a Korean ministry. This article focuses on the second half of the 1571 Vilela letter, while a future article will focus on the first half of the same letter.